Improving Understanding and Collaboration of Grade IV Students of SDN Pulau Tiga through Discovery learning in Social Science Subjects - Yulianti Barung; Jamaludin Jamaludin; Iskandar Iskandar (LP. Ma'arif Janggan Magetan, 2025)
This study aims to improve students' understanding and collaboration skills through the application of the Discovery Learning model in fourth-grade science at Pulau Tiga Public Elementary School, Sombori Islands District, Morowali Regency, Central Sulawesi. The study used a descriptive qualitative approach, with one principal, one class teacher, one science teacher, and fifteen students as subjects. Data collection techniques included observation, interviews, tests, and questionnaires. The study showed a significant increase in student understanding, with an average N-Gain score of 0.5 (moderate category). The greatest improvement occurred in material contextualized to the students' environment. Furthermore, students' collaboration skills also improved, with an average N-Gain score of 0.4 for the contribution, time management, and problem-solving indicators. These findings demonstrate the effectiveness of the Discovery Learning model in improving elementary school students' conceptual understanding and collaboration skills in remote island areas. These findings provide practical implications for teachers in developing locally relevant learning strategies and opportunities for education policy in remote areas.